2003
DOI: 10.1029/2003gl017308
|View full text |Cite
|
Sign up to set email alerts
|

The fate of mercury species in a sub‐arctic snowpack during snowmelt

Abstract: An extensive mercury study was conducted in April 2002 prior to and during the annual melting of a snowpack in a sub‐arctic site along the Hudson Bay (Canada). Gas‐phase measurements show that the snowmelt coincides with an elemental mercury (Hg°) pulse in the snowpack air far above ambient levels. Additional measurements of inorganic mercury (Hg2+) and methylmercury (MeHg+) in snow pits, in surface snow and in a meltwater sample clearly reveal that most of Hg is removed from the snow during the first days of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
138
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(141 citation statements)
references
References 13 publications
3
138
0
Order By: Relevance
“…[76] In Amituk Lake in the Canadian High Arctic, snowmelt delivered the most THg during spring in June and early July [22,77] but 59 % of the THg delivered to Amituk Lake during the snowmelt period was directly discharged through lake outflow because of the limited mixing between surface and underlying water. [22] In Arctic regions, melt water concentrations of MeHg and THg were found to be elevated above full-column snowpack values at the onset of snow melt in some locations, [20,[77][78][79] but not all. [28] A summary of meltwater THg concentrations reported by six studies at nine sites across the Canadian and Greenland Arctic revealed a range from 0.3 to 10 ng L À1 with an average of ,3 ng L À1 .…”
Section: Since 1993 Prof Henrik Skov Has Worked As Principal Scientimentioning
confidence: 99%
See 1 more Smart Citation
“…[76] In Amituk Lake in the Canadian High Arctic, snowmelt delivered the most THg during spring in June and early July [22,77] but 59 % of the THg delivered to Amituk Lake during the snowmelt period was directly discharged through lake outflow because of the limited mixing between surface and underlying water. [22] In Arctic regions, melt water concentrations of MeHg and THg were found to be elevated above full-column snowpack values at the onset of snow melt in some locations, [20,[77][78][79] but not all. [28] A summary of meltwater THg concentrations reported by six studies at nine sites across the Canadian and Greenland Arctic revealed a range from 0.3 to 10 ng L À1 with an average of ,3 ng L À1 .…”
Section: Since 1993 Prof Henrik Skov Has Worked As Principal Scientimentioning
confidence: 99%
“…[245] In contrast, it is now well established that the Hg deposited during AMDEs can be readily re-emitted from the snowpack during winter conditions following AMDEs [7,16,25,80,101,187,241,[246][247][248] and during snow metamorphism and melt. [20,79] Establishing a link between AMDEs and enhanced Hg levels in Arctic biota is complicated partly by a poor understanding of the net outcome of the AMDE deposition pathway, and partly by the complex Hg biogeochemistry of aquatic marine and fresh water ecosystems that contain inorganic Hg II from a variety of sources (of which AMDEs are but one) and methylate the inorganic Hg II into MeHg. Three lines of evidence pertaining to this question are reviewed here: the bioavailability of AMDE-deposited Hg, the amounts and fate of inorganic Hg inputs from AMDEs compared with those from other entry pathways and comparison of the spatial patterns of AMDE occurrence and biotic Hg concentrations.…”
Section: Eastern Beaufort Sea Belugamentioning
confidence: 99%
“…Similarly, Outridge et al (2008) concluded that there is no firm evidence that AMDEs exert a significant influence on mercury concentrations in the Arctic Ocean. However, Lindberg et al (2002), Dommergue et al (2003), Loseto et al (2004), Bargagli et al (2005), , Faïn et al (2007), Brooks et al (2008a), Douglas et al (2008), , Mitchell et al (2008b), Hirdman et al (2009), and Dommergue et al (2010), who conducted field campaigns at a variety of polar and lower latitudes, all determined that mercury deposited onto snowpacks was only partially revolatilized and could have an important impact on the environment. The partial revolatilization was reported for mercury deposited both in and not in association with AMDEs.…”
Section: Introductionmentioning
confidence: 99%
“…At the onset of snowmelt, the rates of photoreduction and revolatilization of GEM to the atmosphere increase significantly (Dommergue et al, 2003;Faïn et al, 2007;Sommar et al, 2007;Brooks et al, 2008b;Douglas et al, 2008), causing…”
Section: Introductionmentioning
confidence: 99%
“…Greenland surface air temperature trends, including at the Summit site, have not shown persistent warming since 1930 in contrast to global average surface temperature (23). Liquid water in snowpacks could enhance GEM emission (e.g., during snowmelt) (26), but occurrences of surface snow melting at Summit are extremely improbable. Similarly, important changes in solar irradiation at Summit during the last century are unlikely.…”
mentioning
confidence: 99%